The cost effectiveness of REACH-HF and home-based cardiac rehabilitation compared with the usual medical care for heart failure with reduced ejection fraction: A decision model-based analysis. (August 2019) - Taylor, Rod S; Sadler, Susannah; Dalal, Hasnain M; Warren, Fiona C; Jolly, Kate; Davis, Russell C; Doherty, Patrick; Miles, Jackie; Greaves, Colin; Wingham, Jennifer; Hillsdon, Melvyn; Abraham, Charles; et al.
Background: The REACH-HF (Rehabilitation EnAblement in CHronic Heart Failure) trial found that the REACH-HF home-based cardiac rehabilitation intervention resulted in a clinically meaningful improvement in disease-specific health-related quality of life in patients with reduced ejection fraction heart failure (HFrEF). The aims of this study were to assess the long-term cost-effectiveness of the addition of REACH-HF intervention or home-based cardiac rehabilitation to usual care compared with usual care alone in patients with HFrEF. Design and methods: A Markov model was developed using a patient lifetime horizon and integrating evidence from the REACH-HF trial, a systematic review/meta-analysis of randomised trials, estimates of mortality and hospital admission and UK costs at 2015/2016 prices. Taking a UK National Health and Personal Social Services perspective we report the incremental cost per quality-adjusted life-year (QALY) gained, assessing uncertainty using probabilistic and deterministic sensitivity analyses. Results: In base case analysis, the REACH-HF intervention was associated with per patient mean QALY gain of 0.23 and an increased mean cost of £400 compared with usual care, resulting in a cost per QALY gained of £1720. Probabilistic sensitivity analysis indicated a 78% probability that REACH-HF is cost effective versus usual care at a threshold of £20, 000 per QALY gained. Results were similar for home-based cardiac rehabilitation versus usual care. Sensitivity analyses indicate the findings to be robust to changes in model assumptions and parameters. Conclusions: Our cost-utility analyses indicate that the addition of the REACH-HF intervention and home-based cardiac rehabilitation programmes are likely to be cost-effective treatment options versus usual care alone in patients with HFrEF.